ANALISIS FAKTOR YANG MEMPENGARUHI KESEHATAN REPRODUKSI IBU MENIKAH DI USIA REMAJA - Junios, Junios; Aldianita, Wella (Sainstek : Jurnal Sains dan Teknologi, 2012)
This study aims to determine factors influence teenage mothers were married to the mother's reproductive health disorders in Jorong Bukik Apik Nagari Padang Tarok Kabupaten Agam of West Sumatra in 2012. The research method used in population study by the survey technique, where the number of teenage mothers who were married at age totaled 35 peopleBased on the results of the study found that factors influencing maternal age married mother Adolescent reproductive health is the lack of knowledge of the signs of pregnancy, pregnant women are at risk, as well as the lack of check gestation. Mother's knowledge about reproductive health will be improved by providing intensive counseling to these mothers.Key words: reproductive health, Jorong Bukik Apik